THE COMBINED EFFECT OF DIFFERENT FEED ON THE GROWTH AND SURVIVAL OF LEAF FISH LARVAE (Pristolepis grooti) - Sri Hartatik; Hamdan Alawi; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from 12th November to 12th December 2015 in the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Science, University of Riau. The aim of this research was to find out the effect of the different feed combination on the growth and a survival rate of leaf fish (Pristolepis grooti) larvae. The research method used was a completely randomized design (CDR) with four treatment and three replications. Type applied were nauplius Artemia, Tubifex sp, egg yolk, and shrimp pellet.Result indicated that the food combinations did effect the growth and survival rate of leaf fish larvae reared in 15 L recirculation Aquaria for 4 weeks. The best result indicate in P1, naupli Artemia+Tubifex sp produce were 0,25 g Bw, with 1,68 cm TL, spesifik growth rate 5,92 %/day and survival rate with 95 %. The water quality parameters during the research were temperature 26-29oC, pH 5,5-6,1 and DO 4,2-5,9 mg/L.Keyword : Pristolepis grooti, food combination, growth and survival rate.